1986
DOI: 10.1056/nejm198607173150303
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Acid-Base State between Venous and Arterial Blood during Cardiopulmonary Resuscitation

Abstract: We investigated the acid-base condition of arterial and mixed venous blood during cardiopulmonary resuscitation in 16 critically ill patients who had arterial and pulmonary arterial catheters in place at the time of cardiac arrest. During cardiopulmonary resuscitation, the arterial blood pH averaged 7.41, whereas the average mixed venous blood pH was 7.15 (P less than 0.001). The mean arterial partial pressure of carbon dioxide (PCO2) was 32 mm Hg, whereas the mixed venous PCO2 was 74 mm Hg (P less than 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1
9

Year Published

1987
1987
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(124 citation statements)
references
References 9 publications
3
109
1
9
Order By: Relevance
“…The loss of blood flow caused by CA is widely acknowledged to cause a metabolic pathology, but we struggle to measure the effect of this pathology at the bedside. The cessation of blood flow during CA stops delivery of metabolic substrates and removal of metabolic waste products, rapidly causing a variety of metabolic disorders including loss of ATP, acidemia, hypercarbia, hyperlactemia, loss of the adenosine pool, loss of ion gradients, and loss of water control 5, 6, 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…The loss of blood flow caused by CA is widely acknowledged to cause a metabolic pathology, but we struggle to measure the effect of this pathology at the bedside. The cessation of blood flow during CA stops delivery of metabolic substrates and removal of metabolic waste products, rapidly causing a variety of metabolic disorders including loss of ATP, acidemia, hypercarbia, hyperlactemia, loss of the adenosine pool, loss of ion gradients, and loss of water control 5, 6, 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…Se postula que la hipercapnia venosa ocurriría al ser tamponados los hidrogeniones producidos por el metabolismo anaerobio, para mantener el equilibrio ácido-base en células con un potencial redox disminuido. Así como la pCO 2 arterial depende de la ventilación alveolar y del intercambio gaseoso pulmonar, la pCO 2 venosa depende del flujo circulatorio y no necesariamente de la hipoxia hipoxémica, correlacionándose inversamente al GC en falla circulatoria 14,[21][22][23][24][25][26][27][28][29][30] , hallazgo reafirmado en este modelo pediátrico. Concordantemente se ha propuesto un rol de la ΔVACO 2 en guiar la terapia de reanimación, de manera complementaria a la saturación venosa central de oxígeno 13 .…”
Section: Discussionunclassified
“…As then, several authors have reported increased dCO 2 in different low flow states [40][41][42]. In oxygen debt caused anaerobic metabolism, hydrogen ions are generated through the hydrolysis of ATP to ADP and increased production of lactic acid [43]. These hydrogen ions are buffered by bicarbonate presented in the cells, and this process will generate CO 2 production [44].…”
Section: Parameters Reflecting Vomentioning
confidence: 99%